Monetary and Financial Statistics Manual and Compilation Guide - Cartas, Jose (Manuals and Guides, 2017)
This edition of Monetary and Financial Statistics Manual and Compilation Guide (Manual) updates and merges into one volume methodological and practical aspects of the compilation process of monetary statistics. The Manual is aimed at compilers and users of monetary data, offering guidance for the collection and analytical presentation of monetary statistics. The Manual includes standardized report forms, providing countries with a tool for compiling and reporting harmonized data for the central bank, other depository corporations, and other financial corporations.